Social Pathology in Organizations: A Systematic Literature Review of Dysfunction, Power, and Symbolic Responsibility - Erni Rusyani (International Journal of Business, Law, and Education, 2026)
This study examines social pathology in organizations and its role in shaping organizational behavior. Social pathology is understood as dysfunctional social, cultural, and structural conditions that weaken ethical conduct, trust, accountability, participation, and organizational legitimacy. Using a structured literature review design, this study analyzed articles retrieved from Scopus through a search strategy combining terms related to pathology, social problems, organizational dysfunction, and organizational contexts. The initial search produced 5,662 records. After applying inclusion criteria related to publication year, language, document type, subject area, and topical relevance, 10 journal articles were selected as the final corpus for analysis. The selected studies were analyzed thematically. The findings show that social pathology in organizations appears through four major patterns: organizational hypocrisy and symbolic social actions, governance failure and organizational dysfunction, social exclusion and power imbalance, and organizational responses to social problems and sustainability. The review suggests that social pathology should not be understood merely as individual misconduct but as a multi-level organizational condition shaped by discourse-practice gaps, weak governance, unequal power relations, exclusionary practices, and symbolic responsibility. This study contributes to organizational behavior literature by offering an integrated conceptual understanding of how pathological social conditions emerge, operate, and can be addressed within organizational settings.